2009
DOI: 10.1016/j.jcrs.2009.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Keratoconus: Classification scheme based on videokeratography and clinical signs

Abstract: PURPOSE To determine in a longitudinal study whether there is correlation between videokeratography and clinical signs of keratoconus that might be useful to practicing clinicians. SETTING Cornea-Genetic Eye Institute, Cedars-Sinai Medical Center, Los Angeles, California, USA. METHODS Eyes grouped as keratoconus, early keratoconus, keratoconus suspect, or normal based on clinical signs and videokeratography were examined at baseline and followed for 1 to 8 years. Differences in quantitative videokeratograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(79 citation statements)
references
References 14 publications
1
74
0
4
Order By: Relevance
“…A KISA% index value of 100% was reported to be highly sensitive and specific for diagnosing keratoconus, and a value between 60 and 100 was suggested to indicate keratoconus suspect [8]. Furthermore, it was suggested that the use of topography-based quantitative variables significantly improved the repeatability, reliability and reproducibility of the diagnostic indices as in above-mentioned studies [17].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A KISA% index value of 100% was reported to be highly sensitive and specific for diagnosing keratoconus, and a value between 60 and 100 was suggested to indicate keratoconus suspect [8]. Furthermore, it was suggested that the use of topography-based quantitative variables significantly improved the repeatability, reliability and reproducibility of the diagnostic indices as in above-mentioned studies [17].…”
Section: Discussionmentioning
confidence: 92%
“…Corneal topography is an essential tool for diagnosing corneal ectatic disorders [15][16][17]. With an increase in refractive surgeries, accurate interpretation of corneal topographic outcomes has become critical.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports in the peer-review literature lately, regarding the keratectasia and keratoconus assessment 17 and progression monitoring, 18,19 as well as postoperative follow-up due to various CXL interventions. 20 The current options of the clinical investigator include quantitative evaluation of corneal morphologic parameters 21 derived from topography 22,23 or Scheimpflug topometry.…”
Section: Discussionmentioning
confidence: 99%
“…10 Several classification systems for keratoconus have been proposed. [11][12][13][14][15][16][17][18][19] The Amsler-Krumeich (AK) system is amongst the oldest and still widely used. In the AK system, the severity of keratoconus is graded from stages I-IV using spectacle refraction, central keratometry, presence or absence of scarring, and central corneal thickness.…”
Section: Introductionmentioning
confidence: 99%